2019
DOI: 10.3390/agronomy9100569
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals the Temporal and Spatial Changes in Physiological Process and Gene Expression in Common Buckwheat (Fagopyrum esculentum Moench) Grown under Drought Stress

Abstract: Common buckwheat is a traditional alternative crop that originated from the northwest of China and is widely cultivated worldwide. However, common buckwheat is highly sensitive to drought stress, especially at the seedling stage, and the molecular mechanisms underlying the response to drought stress still remain elusive. In this study, we analyzed the stress phenotypes of buckwheat seedlings under drought condition. The results showed the wrinkled cotyledon due to the decrease of relative water content (RWC) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 66 publications
2
11
1
Order By: Relevance
“…PAL, C4H, and 4CL are key genes in the early stages of lignin and flavonoid biosynthesis (Martens and Mithöfer, 2005). In Fagopyrum esculentum Moench, lignin increases cell wall thickness to prevent water loss and improve drought resistance (Hou et al, 2019). In our study, we found that coumaric acid, coniferol, (E)-p-coumaric acid, and 4-hydroxy-3-methoxy cinnamaldehyde were upregulated in DSB vs. DSC, and five genes related to lignin were also identified.…”
Section: Underlying the Responses Of Phenylpropanoid Biosynthesis And Purine Metabolism In D Sinense To Drought Stressmentioning
confidence: 53%
See 1 more Smart Citation
“…PAL, C4H, and 4CL are key genes in the early stages of lignin and flavonoid biosynthesis (Martens and Mithöfer, 2005). In Fagopyrum esculentum Moench, lignin increases cell wall thickness to prevent water loss and improve drought resistance (Hou et al, 2019). In our study, we found that coumaric acid, coniferol, (E)-p-coumaric acid, and 4-hydroxy-3-methoxy cinnamaldehyde were upregulated in DSB vs. DSC, and five genes related to lignin were also identified.…”
Section: Underlying the Responses Of Phenylpropanoid Biosynthesis And Purine Metabolism In D Sinense To Drought Stressmentioning
confidence: 53%
“…In addition, most flavonoids were significantly upregulated in DSB vs. DSC even though we did not identify DEGs associated with flavonoid biosynthesis. However, previous research has shown that genes related to flavonoid biosynthesis were upregulated in buckwheat under drought stress (Hou et al, 2019). It is also suspected that flavonoids have antioxidant properties (Sarker and Oba, 2018).…”
Section: Underlying the Responses Of Phenylpropanoid Biosynthesis And Purine Metabolism In D Sinense To Drought Stressmentioning
confidence: 99%
“…The irruption of transcriptomics, metabolomics, high-throughput DNA sequencing and high-density microarrays in the analysis of plants' responses to stress have brought new insights and allowed a better understanding on plants reactions to stressful conditions [21]. The stress-responding genes and their regulation pattern under drought were analyzed in common buckwheat cotyledons and roots [22] and female panicles in maize [23], and under salinity in roots and leaves of pomegranate [24].…”
Section: Drought and Salinitymentioning
confidence: 99%
“…At present, RNA-Sequencing (RNA-Seq) can provide increasing amount of information on differentially expressed genes, transcript structures, new transcripts and isomers, RNA alternative splicing and allele-speci c expression etc [57]. RNA-Seq has been successfully applied to cuckoo, Yerba Mate and cotton [1,10,21], as well as many crop plants such as lentils, buckwheat and millet [23,32,64], to analyze their molecular mechanisms of drought resistance.…”
Section: Introductionmentioning
confidence: 99%